Convergence in Structure and Productivity in European Manufacturing? - Klaus Gugler; Michael Pfaffermayr (Austrian Institute of Economic Research (WIFO), 2000)
We find very fast convergence in productivity for the 99 3-digit European industries over the 1985-1998 period. According to our estimates half of any productivity gap is closed on average in 10 years. The speed of convergence is much higher than obtained previously in the literature. Convergence in industrial structure is, however, much slower than productivity catch up. Skill intensity fastens structural adjustment but seems to have no effect on convergence in productivity. The Heckscher-Ohlin model but also agglomeration effects and path-dependency may explain the puzzling result of rapid productivity convergence but slow or even non-existent convergence in structure.
Keywords: D90; L60; F15; 330; Growth of industries; European integration; convergence; panel estimates; Strukturwandel; Produktivität; Europa